Fostering collaborative research for rare genetic disease: the example of niemann-pick type C disease. Issue 1 (December 2016) - Walkley, Steven; Davidson, Cristin; Jacoby, Jonathan; Marella, Philip; Ottinger, Elizabeth; Austin, Christopher; Porter, Forbes; Vite, Charles; Ory, Daniel
Abstract Rare disease represents one of the most significant issues facing the medical community and health care providers worldwide, yet the majority of these disorders never emerge from their obscurity, drawing little attention from the medical community or the pharmaceutical industry. The challenge therefore is how best to mobilize rare disease stakeholders to enhance basic, translational and clinical research to advance understanding of pathogenesis and accelerate therapy development. Here we describe a rare, fatal brain disorder known as Niemann-Pick type C (NPC) and an innovative research collaborative known as Support of Accelerated Research for NPC (SOAR-NPC) which illustrates one pathway through which knowledge of a rare disease and its possible treatments are being successfully advanced. Use of the "SOAR" mechanism, we believe, offers a blueprint for similar advancement for many other rare disorders.